Changing clinico-epidemiology of post-kala-azar dermal leishmaniasis (PKDL) in India: Results of a survey in four endemic states - Suman Saurabh; Pritam Roy; Dhruv K Pandey; Dipanjan Ray; Shourabh Tarak; Rajesh Pandey; Dileep Kumar; Sarosh Jamil; Anand Paulraj; Amarendra Kumar; Siddhartha Dutta (Journal of Vector Borne Diseases, 2020)
Background & objectives: Detection and treatment of post-kala-azar dermal leishmaniasis (PKDL) cases is considered important for kala-azar elimination. The objective of our study was to find out the proportion of different forms of lesions, interruption of treatment and rate of treatment completion, cure rates of PKDL, risk factors for developing severe forms of PKDL and utilization of services offered by the kala-azar elimination program. Methods: A cross-sectional survey of PKDL patients registered for treatment at all levels of care during 2015 and 2016 was done. Results: 576 PKDL patients who had started treatment in 2015 and 2016 were studied. Three-fourths of all patients were found to be clinically cured after a year of follow-up. Around 90% lesions were of macular type. Interruption of treatment was observed in one-fourth of PKDL patients. Median duration between kala-azar treatment and development of PKDL was 4.5 years. Around 79% patients had past history of kala-azar treatment. Discontinuation of treatment during earlier kala-azar episode was significantly associated with the development of papular and nodular forms of lesion. 43% of patients had received the incentive of INR 2000 after completion of treatment. Around three-fourths women in the reproductive age group were found not to use any contraceptive method during PKDL treatment. Interpretation & conclusion: PKDL treatment interruption should be reduced through ensuring drug supply and timely retrieval of patients. Directly observed treatment should be implemented and combination regimen should be explored to improve final cure rate. Delivery of financial incentive to PKDL patients and counselling and contraception to women of reproductive age group should be improved.